PsycEXTRA Dataset 1994
DOI: 10.1037/e669222012-001
|View full text |Cite
|
Sign up to set email alerts
|

Personality Profiles of U.S. Navy Sea-Air-Land ( SEAL) Personnel

Abstract: 5047Appwo for publc rom: duftbm un itd. Report 94-8, supported by the Naval Medical Research and Development Command, Department of the Navy under work unit 62233N MM33P30.002-6005. The views expressed in this article are those of the author(s) and do not reflect the official policy or position of the Department of the Navy, the Department of Defense, or the U.S. Government. Approved for public release; distribution is unlimited. NAVAL HEALTH RESEARCH CENTER SUMMARY Problem.High (50-70%) attrition rates among … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
16
3

Year Published

2000
2000
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 2 publications
4
16
3
Order By: Relevance
“…Braun, Prusaczyk, Goforth, and Pratt (1994) administered a five factor survey (NEO Personality Inventory) comparing SEAL recruits to males in the general population in five categories: conscientiousness, neuroticism, extraversion, agreeableness, and openness. Findings revealed that SEALs scored lower than the general population on neuroticism, indicating they are less prone to feelings of depression and vulnerability, and higher on aspects of extraversion such as excitement seeking and assertiveness.…”
Section: Text-based Analysismentioning
confidence: 99%
“…Braun, Prusaczyk, Goforth, and Pratt (1994) administered a five factor survey (NEO Personality Inventory) comparing SEAL recruits to males in the general population in five categories: conscientiousness, neuroticism, extraversion, agreeableness, and openness. Findings revealed that SEALs scored lower than the general population on neuroticism, indicating they are less prone to feelings of depression and vulnerability, and higher on aspects of extraversion such as excitement seeking and assertiveness.…”
Section: Text-based Analysismentioning
confidence: 99%
“…For example, McDonald, Norton, and Hodgdon (1988) administered the Hogan Personality Inventory and found that successful SEAL recruits scored higher than drop outs in self-confidence, composure under pressure, amicability, courteousness, and even temperedness. Braun, Prusaczyk, Goforth, and Pratt (1994) administered a five factor survey (NEO Personality Inventory) comparing SEAL recruits to males in the general population in five categories: conscientiousness, neuroticism, extraversion, agreeableness, and openness. Findings revealed that SEALs scored lower than the general population on neuroticism, indicating they are less prone to feelings of depression and vulnerability, and higher on aspects of extraversion such as excitement seeking and assertiveness.…”
Section: Insert Table 3 About Here: Sources Of Videographymentioning
confidence: 99%
“…A study of 139 NEO-PI-R profiles from operators in the United States Navy Sea-Air-Land (SEAL) Commando, found that SEALs had lower scores on neuroticism and agreeableness, the same to lower on openness, and higher scores on conscientiousness and extraversion, relative to the norms for adult American males (Braun et al, 1994). This study also reported that more-experienced SEALs scored higher on conscientiousness and lower on extraversion than lessexperienced SEALs, and that commissioned officers had higher scores on both of these factors when compared to enlisted operators.…”
Section: Introductionmentioning
confidence: 99%